Richard Cumberland letter and prayer - Cumberland, Richard, 1732-1811.
Letter and prayer.
In part, positive photocopy of typewritten transcript.
Dramatist and essayist.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Dramatists; Essayists